Participatory design in education materials in a health care context. Issue 3 (September 2017) - Smith, Frida; Wallengren, Catarina; Öhlén, Joakim
Written patient education material, for example, discharge-information is commonly used in hospital settings. Despite following guidelines on how to best present text and using patients as consultants, improvements can still be made from a patient's perspective. Here, we describe the process of developing patient education material using a participatory design methodology, with patients, clinicians, researchers and designers working as co-designers following a structured process map. The method emphasises coping with conflicting interests and using this as a source of development. The philosophies behind action research and person-centred care were combined in a practical setting, enhancing both perspectives and generating actionable knowledge to be further used in patient involvement projects. The results reveal that predominant areas of tensions focused on power, organization, content and clinical usability. This study is one of the first to involve patients as co-designers of education materials in the health care context, and not only as consultants. Working as co-designers was found to be productive and in line with person-centred care philosophy, with focus on partnership and equality. The results of this study can therefore benefit both patients and other relevant stakeholders in the healthcare system in developing written patient education materials.